Management of chronic musculoskeletal pain in veterans: a systematic review - Santini, Alessandro; Petruzzo, Antonio; Giannetta, Noemi; Ruggiero, Antonio; Di Muzio, Marco; Latina, Roberto (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work. Veterans are military with health problems due to military conditions. The improved body armor and operational conditions has reduced the number of deaths, but increased the number of veterans with severe injuries, affected by musculoskeletal pain and associated syndromes, such as post-traumatic stress disorder. Multimodal approaches are considered in USA the gold standard for the treatment of these problems, while in Europe and Italy the data are unknown. The aim of this review was to describe and summarize multimodal therapeutic approaches that apply to the veteran population for chronic musculoskeletal pain and relate syndromes management.Methods. A comprehensive systematic review of the literature on Cochrane Library, PubMed, CINAHL e PsycINFO databases was conducted, from 2001 to 2020.Results. 228 papers have been found, 134 were selected after the first screening. 24 quantitative studies were included in the review, all from USA. Different multimodal interventions with different kind of treatment types emerged. The analyzed studies’ sample size was 11 million (mean age = 57.67 years; SD=±11.94). The multimodal approaches showed a significant improvement in all outcomes (pain reduction and control, opioid therapy reduction, psychosocial outcomes) compared to traditional therapy.Conclusions. Multimodal therapeutic approaches seem to guarantee a good management chronic musculoskeletal pain and related mental disorders, and the reduction and control to opioid use. Military nurses emerged as professionals who have a central role in this approach. European and Italian authorities should consider veterans, in order to assess their expected increase in the future.